Skema Bunga Bank Menurut Hermeneutika Abdullah Saeed (Telaah Ayat-Ayat RibÄ) - Misnawati Misnawati; Cut Zainab (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
Bank Interest Scheme According to Abdullah Saeed's Hermeneutics (Examination of RibÄ Verses)Abdullah Saeed is famous person because his thoughts on contextual interpretation, his journals is frequently awaited by academics. He is still alive today, his thoughts on the interpretation of the Quran are also quite easy to understand. This studyÂ  is a library research with using a hermeneutic approach for examining the bank interest scheme intended by Abdullah Saeed. The most of the data in this study used from Abdullah Saeedâ€™s books and journals and also several other references is research about interpretation contextualist of Abdullah Saeed. According to Abdullah Saeed, the verses of the Quran that different from currently concept of bank interest now. Bank interest which mean clearly forbidden is the presence of elements of oppression and harming other. It is absolutely different from bank interest, are creditors at bank are mostly those who can afford and have agreed to pay more voluntarily. This makes bank interest not include usury as the Quranâ€™s explaining. The thoughts of Abdullah Saeed are based on the concept of revelation that he coined, that Allah's revelation will not increase Rasulullah has died, but the reasoning from these revelation must till develop according to the needs of the times